Wanda hears the stars : a blind astronomer listens to the universe - Hansen, Amy; Díaz Merced, Wanda (Charlesbridge, 2025)
"Growing up in Puerto Rico, Wanda Díaz Merced wanted to study the stars. But when she lost her sight, she had to find a new way to work. Through the use of sonification, which turns data into sound, she was able to make a path for herself and other scientists with disabilities."--